2020
DOI: 10.3390/nu12061583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 Home Confinement on Eating Behaviour and Physical Activity: Results of the ECLB-COVID19 International Online Survey

Abstract: Background: Public health recommendations and governmental measures during the COVID-19 pandemic have resulted in numerous restrictions on daily living including social distancing, isolation and home confinement. While these measures are imperative to abate the spreading of COVID-19, the impact of these restrictions on health behaviours and lifestyles at home is undefined. Therefore, an international online survey was launched in April 2020, in seven languages, to elucidate the behavioural and lifestyle conseq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

175
1,525
34
104

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 1,684 publications
(2,017 citation statements)
references
References 27 publications
175
1,525
34
104
Order By: Relevance
“…Although it is an effective solution to slow the spread of infectious diseases, home confinement can also have negative effects on mental health and multiple lifestyle behaviors including social participation and life satisfaction. Indeed, recent multicenter studies showed that COVID-19 home confinement evoked an increased number of individuals who are physically inactive (+15.2%) [ 18 , 19 ], exhibiting unhealthy dietary behaviors (+10%) [ 18 , 19 ], and experiencing psychosocial and emotional disorders (+10% to +16.5%, respectively) as well as poor sleep quality (12.8%) [ 18 , 20 ] during home confinement. Regarding, social participation and life satisfaction, it was recently suggested that the COVID-19 crisis and the associated confinement may also be associated with sensations of loneliness, grief, and loss of life satisfaction [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is an effective solution to slow the spread of infectious diseases, home confinement can also have negative effects on mental health and multiple lifestyle behaviors including social participation and life satisfaction. Indeed, recent multicenter studies showed that COVID-19 home confinement evoked an increased number of individuals who are physically inactive (+15.2%) [ 18 , 19 ], exhibiting unhealthy dietary behaviors (+10%) [ 18 , 19 ], and experiencing psychosocial and emotional disorders (+10% to +16.5%, respectively) as well as poor sleep quality (12.8%) [ 18 , 20 ] during home confinement. Regarding, social participation and life satisfaction, it was recently suggested that the COVID-19 crisis and the associated confinement may also be associated with sensations of loneliness, grief, and loss of life satisfaction [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The unprecedented coronavirus disease (COVID-19) pandemic has created vast socioeconomic burdens [ 1 ], morbidity, and mortality [ 2 , 3 ]. The pandemic has also changed eating behaviors for the worse [ 4 , 5 , 6 , 7 ]. To deal with this challenge, the USA National Institute of Health Nutrition Research Task Force developed a 2020–2030 strategic plan to improve health and prevent or combat diseases and conditions that have been affected by food and nutrition [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stay-at-home orders, self-isolation, and social distancing measures are crucial to flatten the curve of this disease. However, these measures are having negative impacts, including reduced physical activity, unhealthy eating, and weight gain [19] . These changes in lifestyle have numerous pathophysiological effects, including promoting insulin resistance via a range of well-described mechanisms, including triggering inflammatory pathways, which would presumably increase the risk of new-onset diabetes in high-risk individuals.…”
mentioning
confidence: 99%